Observation on advertising cosmetic and supplementary products : from perspective of Qawaid Fiqhiyah / Nur Athirah Azmi - Azmi, Nur Athirah (2019)
Advertising is an essential element of promoting a product within a business. This is because the advertisers may introduce brand products provided by them to the public. In that way they can also influence a person's thinking and indirectly attract more people to get and consume their product. However, there have been many issues in advertising where advertisers do not adhere to established guidelines especially advertising of cosmetic and supplement products. The method used was based on the qualitative methods that consist of library research, observation, and data analysis. Therefore, this study will focus more on advertising itself and provide guidelines for Islamic advertising as additional information. Then take the existence cases of advertising cosmetic and supplement products in Malaysia to study from the perspective of Qawaid Fiqhiyah as a result of this research.